Effectiveness of school-based self-management interventions for asthma among children and adolescents: findings from a Cochrane systematic review and meta-analysis. Issue 5 (27th January 2019) - Kneale, Dylan; Harris, Katherine; McDonald, Vanessa M; Thomas, James; Grigg, Jonathan
Abstract : Introduction: The evidence that teaching self-management techniques to children and young people with asthma in schools is effective has not, to date, been the subject of systematic review. Methods: We conducted a systematic review of intervention studies. Studies were eligible if they employed a randomised parallel-group design and were published in English from 1995 onwards. Participants included children with asthma aged 5–18 years who participated within their own school environment. Searches were conducted on the Cochrane Airways Group Specialised Register. Quantitative data were combined using random-effects meta-analyses. Results: Thirty-three outcome evaluation studies were included. School-based interventions were effective in reducing the frequency of emergency department visits (OR 0.70, 95% CI 0.53 to 0.92; studies=13), and moderately effective in reducing levels of hospitalisations (standardised mean differences [SMD] −0.19, 95% CI −0.35 to −0.04; studies=6). A meta-analysis of three studies suggest that the intervention approach could reduce the number of days of restricted activity (SMD −0.30, 95% CI −0.41 to −0.18; studies=3). However, there was uncertainty as to whether school-based self-management interventions impacted on reducing absences from school. Conclusions: Self-management interventions for children with asthma delivered in schools reduce the number of acute episodes of healthcare usage. We conclude that the school environment is an important space for delivering interventions to improve children's health.